Hip adduction and abduction strength recovery in senior male rugby union players during a full training and match week - O`Connor, C.; Coyle, E.; McIntyre, M.; Delahunt, E.; Thorborg, K. (Physical Therapy in Sport, 2026)
Objectives To report hip adduction and abduction strength recovery of rugby players during a full training and match-week, and to examine the relationship between session load, daily hip/groin pain, and provoked groin pain, on changes in hip strength.